Study of double parton scattering using four-jet scenarios : in proton-proton collisions at √s = 7 TeV with the CMS Experiment at the LHC /: in proton-proton collisions at √s = 7 TeV with the CMS Experiment at the LHC. ([2016]) - Gunnellini, Paolo
No abstract available